Elevated visfatin levels illuminate the inflammatory path in bronchopulmonary dysplasia - Berna Hoti; Gizem Özcan; Nazan Çobanoğlu; Seda Topçu; Filiz Bakar Ateş (The Turkish Journal of Pediatrics)
Background. Bronchopulmonary dysplasia (BPD) is a chronic lung disease in premature infants caused by an imbalance between lung injury and lung repair in the developing immature lungs of the newborn. Pulmonary inflammation is an important feature in the pathogenesis of BPD. The aim of this study was to evaluate the relationship between the inflammatory microenvironment and the levels of visfatin and nesfatin-1, which are among the new adipocytokines, in BPD patients.